(3GdeSDhdjI GdLHGFjI deSjQj GdTQcGJ (B/s - (3Hf RGQY, QGHMs ((3GdLRGFQ(B: s (3OGQ GdYdhe ddfTQ hGdJhRjY(B, s, 2014)
(3jJfGhd fWGb GdeSDhdjI GdLHGFjI deSjQj GdTQcGJ, JbQjQ eSDhdjI eSjQ GdTQcI LHGFjG(B.s
(3HjHdjhZQGajG(B: (3U U(B.189-193s
Keywords: (3GdTQcGJs; (3GdVQGFHs; (3GdVQGFH(B- (3bhGfjf hJTQjYGJs